Choosing appropriate responses to groundwater depletion - International Water Management Institute (International Water Management Institute, 2006)
This Water Policy Briefing is based on Policies Drain the North China Plain: Agricultural Policy and Groundwater Depletion in Luancheng County, 1949 ? 2000 (IWMI Research Report 71) by Eloise Kendy, David J. Molden, Tammo S. Steenhuis, Changming Liu and Jinxia Wang and on Hydronomic Zones for Developing Basin Water Conservation Strategies (IWMI Research Report 56) by David J. Molden, R. Sakthivadivel and Jack Keller. With growing populations, changing weather patterns, and increasing pollution of surface water bodies, countries across the world are relying more and more on finite groundwater reserves built up over centuries, for household, agricultural, and industrial needs. Although addressing water shortages in the short term, groundwater exploitation brings with it its own host of problems. It can cause salt water intrusion into fresh water aquifers and subsidenceof the land surface. Governments are quick to turn to improving water efficiency as the best solution to the problem, but are too often disappointed. Research is increasingly highlighting that in devising water management strategies to conserve water and halt the decline of groundwater levels, policymakers must conduct holistic studies of hydrologic systems to find appropriate solutions that will result in real water savings. What?s needed then is not a simple ?one size fits all? policy or solution, but varying management approaches to suit specific situations. The concept of hydronomic zones, which categorizes a hydrologic system into different zones?each having its own water-related issues?could be a useful tool in this exercise.